Comparative study of the electrical performance of three types of photovoltaic technologies in Rabat and Errachidia station. (2022) - El Hajjam, Nablous; Hartiti, Bouchaib; Barhdadi, Abdelfettah; Habchi, Abderrahim; Lfakir, Abderrazak; fadili, Salah; Batan, Abdelkrim; Faddouli, Ali; Thévenin, Philippe
Abstract: The production of electricity by the photovoltaic systems is an idea that has been applied for many years. In this paper, the annual AC power, total AC power of three kinds of photovoltaic systems (Monocrystalline, polycrystalline, amorphous silicon) were calculated and discussed in Rabat and Errachidia stations, located approximately 316.61 km apart, over the year 2018. The photovoltaic (PV) systems were installed in order to determine which technology produces the most clean electricity. It is based on a comparison of the monthly production of the three technologies in the two cities, and the justification of the behaviour of the three technologies using two similar weather stations installed near the solar panels. In such a way, the determination of the climatic conditions will justify the behaviour of the three technologies. The comparative analysis included annual energy efficiency, performance ratio, annual energy density and system efficiency. Thus, with these performances, we can observe that photovoltaic installations with polycrystalline are appropriate in Errachidia, whereas in Rabat they are monocrystalline. Also, the photovoltaic system of Errachidia stations is more efficient as compared with Rabat stations.